Respuesta :
Answer: ( p - q)(2)(p - q )(2) = 4 p² - 8 p q + 4 q²
Step-by-step explanation:
We have expression ( p - q ) (2) ( p - q ) (2)
Here all the parenthesis are in multiplication .
First we multiply the constant 2 with the terms inside the parenthesis ( p - q) ,
we get
( 2p - 2 q) ( p - q) (2)
= ( 2p - 2q ) ( 2p - 2q)
Now we need to multiply the two parenthesis together using FOIL method .
( 2p - 2q ) ( 2 p - 2q )
= 2 p ( 2 p - 2 q ) - 2q ( 2p - 2q )
= 2p * 2p - 2p * 2q - 2q * 2p + 2q * 2q
= 4p² - 4 p q - 4 p q + 4 q²
Combining like terms , we get
4p² - 8 pq + 4q²